Diagnostic accuracy of fine-needle aspiration of solid pancreatic lesions guided by endoscopic ultrasound elastography - Facciorusso, Antonio (Ann Gastroenterol, 2018)
BACKGROUND: Real-time elastography (RTE) may increase the diagnostic accuracy of fine-needle aspiration guided by endoscopic ultrasound. The aim of this study was to establish the diagnostic accuracy, sensitivity, and specificity of this combined methodological approach in a cohort of patients with solid pancreatic masses. METHODS: We reviewed data from 54 patients with solid pancreatic lesions referred to our institution between January 2014 and June 2015. RTE, assessed in terms of strain ratio, was performed both qualitatively and semi-quantitatively, and a 25G needle was inserted into the most suspicious part of the lesion. Sensitivity, specificity, diagnostic accuracy, positive and negative predictive values were calculated. RESULTS: The median lesion size was 35 mm (interquartile range: 25-43 mm). A diagnosis of adenocarcinoma was confirmed in 85.1% of cases. RTE, with a strain ratio cutoff of 4.21, showed a sensitivity of 86.9%, a specificity of 75%, and diagnostic accuracy of 85.1%. The diagnostic accuracy, sensitivity, and specificity of the combined methodology were 94.4%, 93.4%, and 100%, respectively. The positive predictive value was 100%, the negative predictive value 72.7% and the negative likelihood ratio 6.5. No severe adverse events were registered. CONCLUSION: The combination of RTE with endoscopic ultrasound-guided fine-needle aspiration appears to be an efficient and safe technique for the characterization of solid pancreatic masses.